2013
DOI: 10.1016/j.wasman.2013.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Decreased PCDD/F formation when co-firing a waste fuel and biomass in a CFB boiler by addition of sulphates or municipal sewage sludge

Abstract: Polychlorinated dibenzo-p-dioxins (PCDDs) and polychlorinated dibenzofurans (PCDFs) are formed during waste incineration and in waste-to-energy boilers. Incomplete combustion, too short residence times at low combustion temperatures (<700 °C), incineration of electronic waste and plastic waste containing chlorine are all factors influencing the formation of PCDD/Fs in boilers. The impact of chlorine and catalysing metals (such as copper and iron) in the fuel on PCDD/F formation was studied in a 12 MW(th) circu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 69 publications
0
14
0
Order By: Relevance
“…The Cl concentration inside the biomass solid waste is known higher that sludge. High amounts of chlorine in the fuel can lead to high emissions of gaseous HCl [22]. Fig.…”
Section: Hcl Emission Patternmentioning
confidence: 99%
“…The Cl concentration inside the biomass solid waste is known higher that sludge. High amounts of chlorine in the fuel can lead to high emissions of gaseous HCl [22]. Fig.…”
Section: Hcl Emission Patternmentioning
confidence: 99%
“…Previous studies have concluded that aluminum compound, such as AlCl 3 and Al 2 O 3 , was an important metal catalyst for PCDD/Fs formation (Chang and Chung 1998;Lu et al 2007). Moreover, high amount of chlorine content in the sludge would provide more chlorine source for PCDD/Fs formation (Addink et al 1998;Gullett et al 2000;Mininni 2004;Åmand and Kassman 2013). However, whether aluminum ion or chlorine is the main factor to influence the formation of PCDD/Fs needs a further study.…”
Section: Resultsmentioning
confidence: 99%
“…Some flocculants contain chlorine source, especially catalytic metals, which may affect the formation of PCDD/Fs during incineration (Gullett et al 2000;Kuzuhara et al 2003;Mininni 2004;Lu et al 2007;Åmand and Kassman 2013). However, there has been to our knowledge no study on the influence of flocculants on the formation of PCDD/Fs in sewage sludge incineration.…”
Section: Introductionmentioning
confidence: 99%
“…Research on characteristics of distribution of their congeners would provide the scientific basis for both reducing the second pollution and improving the treatment technology for the air pollution control process. The formation of PCDD/Fs was related to catalyzing metals and chlorine [59], and the further reduction of acid gases and heavy metals should contribute to controlling the emission of organic pollutants in the flue gas.…”
Section: Emission Levels Of Organic Pollutantsmentioning
confidence: 99%